"The boundary has been moved": Hollywood cinéma-monde, film borders, and the multilingual assassin in Sicario and Inglourious Basterds. Issue 1 (1st March 2022) - King, Gemma
Abstract : Transnational coproductions, multilingual dialogue, and border-crossing of many forms are growing increasingly common in contemporary cinemas. As a result, assigning a nationality to a film can prove a slippery and even arbitrary process. This article takes a new approach to films such as Sicario (Denis Villeneuve 2015) and Inglourious Basterds (Quentin Tarantino 2009 ), analyzing texts traditionally viewed as American through the lens of cinéma-monde (Marshall 2012 ). It focuses in particular on these films' use of maps, and on their strikingly similar multilingual assassination scenes, reading them through Bill Marshall's characterization of a cinema that "dramatically focuses attention on four elements: borders, movement, language, and lateral connections" (42). Each of these films was directed by an established auteur working in a "foreign" space and non-native languages, and each depicts continual border-crossing, code-switching, and violence committed across geographic and linguistic lines. With significant American and other characteristics, neither Sicario nor Inglourious Basterds could be neatly categorized as Quebecois nor French respectively. Yet these films implicate the French-speaking world in diverse ways. Ultimately, the ways in which these films traverse, theorize, and weaponize the border begs a questioning of how far the concepts of national cinemas, and indeed of cinéma-monde, can be extended.